The prevention of disease relapse after allogeneic hematopoietic cell transplantation in acute myeloid leukemia - Maffini, Enrico; Ursi, Margherita; Barbato, Francesco; Dicataldo, Michele; Roberto, Marcello; Campanini, Elena; Dan, Elisa; De Felice, Francesco; De Matteis, Serena; Storci, Gianluca; Bonafè, Massimiliano; Arpinati, Mario; et al. (Frontiers in Oncology, 2022)
Disease relapse represents by far the most frequent cause of hematopoietic cell transplantation (HCT) failure. Patients with acute leukemia suffering relapse after HCT have limited conventional treatment options with little possibility of cure and represent, de facto, suitable candidates for the evaluation of novel cellular and biological-based therapies. Donor lymphocyte infusions (DLI) has been one of the first cellular therapies adopted to treat post HCT relapse of acute leukemia patients and still now, it is widely adopted in preemptive and prophylactic settings, with renewed interest for manipulated cellular products such as NK-DLI. The acquisition of novel biological insights into pathobiology of leukemia relapse are translating into the clinic, with novel combinations of target therapies and novel agents, helping delineate new therapeutical landscapes. Hypomethylating agents alone or in combination with novel drugs demonstrated their efficacy in pre-clinical models and controlled trials. FLT3 inhibitors represent an essential therapeutical instrument incorporated in post-transplant maintenance strategies. The Holy grail of allogeneic transplantation lies in the separation of graft-vs.-host disease from graft vs. tumor effects and after more than five decades, is still the most ambitious goal to reach and many ways to accomplish are on their way.